Efficacy of moxidectin, using various dose regimens, against JYD-34, a macrocyclic lactone resistant isolate of Dirofilaria immitis - Elizabeth M. Martin; Elizabeth B. Mitchell; Stephen Yoon; John W. McCall; Becky Fankhauser; Abdelmoneim Mansour; Scott McCall; Matthias Pollmeier (Parasites & Vectors, 2024)
Abstract Background Macrocyclic lactones (MLs) are the only class of drugs currently commercially available that are effective for preventing heartworm disease. The data presented in this article provide information on the efficacy of oral moxidectin against JYD-34, a known ML-resistant Dirofilaria immitis isolate, when dogs are treated under various dosing regimens. Methods Fifty-two purpose-bred Beagle dogs were used in five laboratory studies. All dogs were inoculated with 50 D. immitis third-stage larvae (L3) (JYD-34 isolate) 30 days prior to the first treatment. Dogs were randomized to treatment (four to five animals in each group) with one, three, or five monthly doses of oral moxidectin ranging from 6 to 100 µg/kg body weight. In each study, control dogs were not treated. Five to 6 months after L3 inoculation, dogs were euthanized, and adult worms were counted to evaluate efficacy of the dosing regimens. Results Adult heartworms were recovered from all control dogs, with an overall geometric mean of 29.7 worms (range 15.2 to 38.0, individual counts ranged from 8 to 51). Five monthly doses of 6 µg/kg provided 83.3% and 90.2%, efficacy, and the same number of monthly doses of 9 µg/kg demonstrated 98.8% and 94.1% efficacy. Three monthly doses of 30 and 50 µg/kg demonstrated 97.9% and 99.0% efficacy, respectively, while a single dose of 100 µg/kg demonstrated 91.1% efficacy. Conclusions Five monthly doses of 9 µg/kg provided similar or only marginally lower efficacy against JYD-34, a known ML-resistant isolate, compared to substantially higher doses administered for 3 months. This underscores the importance of duration of exposure to moxidectin when facing ML-resistant isolates. Repeated administration of lower doses of moxidectin are an alternative to higher doses in the prevention of heartworm disease associated with less susceptible or resistant isolates. Graphical Abstract